KKN-PPM: Improvement of Creativity Processing Purple Uwi into Purple Uwi Chips - Sandy Vikki Ariyanto; Imron Rosyadi NR (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2020)
Based on observations by DPL and KKN students of Madura University, Blaban Village is located on a plateau of rocks that make it difficult to grow plants. The soil condition of Blaban village is barren and dry during the dry season, during the rainy season the soil is cracked so that it needs water absorption to collect rainwater in the soil and improve the structure of the dry soil during the dry season. With a combination of science from soil structure (Geophysical Science), water supply in the soil (Geophysical Science), liquid fertilizer (Agricultural Science), product processing (Industrial Engineering), quality and quantity management (Industrial Engineering and Management Science), financial management (Economics), marketing management (Industrial and Economic Engineering) even taking care of business licenses (Legal and Administrative Sciences), and online sales using applications (Informatics Engineering). In order to maximize the processing of purple uwi into purple uwi chips in Blaban Village, the initial planting of purple uwi to processing as well as selling purple uwi chips are done through offline and online methods. The results obtained are optimizing the sale of purple uwi crops into purple uwi chips, which has more demand by all consumers in various regions.